A numerical simulation study on the characteristics of wrap shell lightweight aggregate concrete based on random aggregate model - Guo Lixia; Yang Yuqing; Zhong Ling; Linfang Lu (Case Studies in Construction Materials)
It is a way to reuse solid waste by using dredged silt as raw material to prepare unburned wrap shell lightweight aggregates and replacing crushed stone aggregate to prepare unburned wrap shell lightweight aggregates concrete specimen. In order to understand the characteristics of wrap shell lightweight aggregates concrete, this paper adopts the method of combining laboratory test and numerical simulation to design the mix ratio test scheme of concrete specimens with different substitution rates of wrap shell aggregate (0 %, 25 %, 50 %, 75 %, 100 %), and conducts indoor mechanical properties test and numerical simulation simulation test on them, so as to obtain and analyze the mechanical properties and failure characteristics.The results show that:(1) The peak stress intensity of concrete specimens decreases linearly with the increase of the substitution rate of wrap shell aggregate.(2) The peak stress of concrete under different wrap shell round aggregate substitution rates is normally distributed, and the dispersion of peak strength decreases with the increase of wrap shell aggregate substitution rate. When the substitution rate is 0 %, the dispersion of peak strength is the largest.(3) Under the uniaxial compression simulation test, the failure mode of concrete specimens changes with the addition of the substitution rate of wrap shell aggregate. When the crack failure occurs, natural coarse aggregate with high strength is chosen to bypass, while when it comes to wrap shell aggregate with low strength, it is chosen to penetrate. With the continuous addition of round aggregate, the stress concentration phenomenon inside concrete can be effectively improved and the number of micro-cracks can be reduced.But at the same time, the penetration cracks gradually increase and gradually tend to be straight.The fractal dimension is negatively correlated with the compressive strength and positively correlated with the substitution rate of wrap shell aggregate.The above research can provide theoretical basis for the popularization of recycled concrete with wrap shell aggregate.